2020
DOI: 10.1080/02705060.2020.1842261
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton functional groups succession and their driving factors in a shallow subtropical lake

Abstract: The succession of phytoplankton functional groups and environmental variables were investigated from January to December 2018 in a shallow subtropical lake, East Taihu Lake, located in the Yangtze Delta of China. Altogether, 125 genera, 21 functional groups, and 7 predominant functional groups, D (Fragilaria acus, Synedra acus, and Nitzschia spp.), P (Fragilaria capucina and Aulacoseira granulate), MP (Oscillatoria spp., Diploneis ovalis, Gomphonema angustatum, Nitzschia palea, and Achnanthes spp.), Y (Cryptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
4
3
0
Order By: Relevance
“…In this study, the dominant functional groups M, H2, MP, and J are all positively correlated with water temperature (WT), and RDA also shows that WT (15%) has the highest interpretation rate of phytoplankton functional groups, indicating that WT is a crucial limiting factor for the dynamics of phytoplankton functional groups in Lake Chaohu. Similar observations have been reported in Lake Santa Lucia, Lake East Taihu, and Lake Okeechobee (Silva et al 2018 ; Nan et al 2020 ; Ma et al 2022 ). In Lake Chaohu, function groups Y and N are dominant in winter, and they are related to low temperature and high turbidity, consistent with the findings of other studies (Xu et al 2011 ; Nan et al 2020 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this study, the dominant functional groups M, H2, MP, and J are all positively correlated with water temperature (WT), and RDA also shows that WT (15%) has the highest interpretation rate of phytoplankton functional groups, indicating that WT is a crucial limiting factor for the dynamics of phytoplankton functional groups in Lake Chaohu. Similar observations have been reported in Lake Santa Lucia, Lake East Taihu, and Lake Okeechobee (Silva et al 2018 ; Nan et al 2020 ; Ma et al 2022 ). In Lake Chaohu, function groups Y and N are dominant in winter, and they are related to low temperature and high turbidity, consistent with the findings of other studies (Xu et al 2011 ; Nan et al 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the relative biomass of dominant functional group H2 rises in autumn and occupies a higher proportion in Location IV. Furthermore, function group MP is mainly composed of Bacillariophyta species in spring but Cyanophyta species in autumn with increasing water temperature and nutrient concentrations; similarly, research findings have been reported in other aquatic ecosystems such as Lake Luoma, Lake East Taihu, and Daning River (Zhu et al 2013 ; Tian et al 2018 ; Nan et al 2020 ). In this study, the dominant functional groups M, H2, MP, and J are all positively correlated with water temperature (WT), and RDA also shows that WT (15%) has the highest interpretation rate of phytoplankton functional groups, indicating that WT is a crucial limiting factor for the dynamics of phytoplankton functional groups in Lake Chaohu.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, Function group MP dominated by Bacillarioplyta species in spring, and it changed to Cyanophyta in autumn with the increase of WT and nutrient concentrations. The same research results were also found in Lake Luoma, Lake East Taihu, and Daning River(Zhu et al, 2013;Tian et al, 2018;Nan et al, 2020). Moreover, the dominant functional groups M, H2, MP and J were all positively correlated with WT in this study, and RDA showed that WT (15%) had the highest interpretation rate of phytoplankton functional groups, indicating that WT was one of the key factors limiting the dynamics of phytoplankton functional groups in Lake Chaohu.…”
supporting
confidence: 86%
“…Moreover, the relative biomass of function group M in Location I was higher than the other three locations (Locations II, III and IV), and a large number of nutrients and exogenous organic substances from Shiwuli River, Nanfei River, and Paihe River were responsible for the water quality of this area(Jiang et al, 2014;Zhong et al, 2019). Usually, functional group H2 grows well under low nitrogen, low light and high phosphorus, and its biomass decreases with rising water levels(Padisák et al, 2006;Nan et al, 2020;Yang et al, 2016). In this study, the relative biomass of H2 rises in autumn and occupies a higher proportion in Location IV.…”
mentioning
confidence: 92%